Stakeholders Mapping Tata Kelola Kerukunan Umat Beragama di Indonesia: (Studi Kasus di Kota Cilegon Provinsi Banten) - kandung sapto nugroho (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2023)
Conflicts in the name of religion in various parts of the world are currently escalating, and Indonesia is no exception. Cilegon City is known as one of the intolerant cities. This article was conducted to identify stakeholders in the governance of religious harmony in Cilegon City, then categorize them and look at interactions between stakeholders. The study was conducted with a qualitative approach. Data collection by interviews, observation and documentation studies while still carrying out the obligation to triangulate data sources and techniques. This study found that there are six stakeholders namely: government, social organizations, mass media, academics, private sector, and quasi-NGOs with six different roles, namely as (1) regulator; (2) facilitators; (3) implementers; (4) evaluators; (5) advocates; and (6) beneficiaries and have four different interests, namely (1) economy; (2) social; (3) politics; and (4) religion. The researcher encourages further studies on the potential and consensus strategies for local wisdom in fulfilling the right to houses of worship in Banten.